The Ability of Patchouli Waste Compost with Trichoderma spp as Biodecomposer in Inhibiting the Development of Budok Disease (Synchtrium pogostemonis) in Patchouli Seedlings - Rina Sriwati; Ramadani Syapitra; Tjut Chamzurni; Jauharlina Jauharlina; Hartati oktarina (Journal of Patchouli and Essential Oil Products, 2022)
Patchouli waste (LAN) from essential oil distillation process is known to have high nutrient content and has potential as raw material for organic fertilizer. In this study, patchouli pulp was used as compost with the addition of biodecomposers of several Trichoderma species (T. harzianum, T.asperellum, T. hamatum, T. virens, and T. atroviride) to inhibit the development of budok disease in patchouli seedlings. Trichoderma spp. inoculated on a mixture of patchouli dregs, bran and manure. The mature LAN compost was mixed into the growing media before artificial inoculation of the pathogen Synchtrium pogostemonis in a 2:1 ratio. Parameters observed were incubation period and percentage of attack. The results showed that patchouli seedlings planted in media containing LAN compost with the biodecomposer T. harzianum did not show symptoms of budok disease until the end of the observation (42 days). LAN compost with T. asperellum biodecomposer was also proven to be able to extend the incubation period from 2.5 days (control) to 5.5 days. The greatest suppression of intensity was seen in the treatment of LAN compost with T. asperellum, T. virens, and T. atroviride biodecomposers, which was 6.25%. The results of this study indicate that the waste of patchouli dregs with the help of the decomposer Trichoderma spp. is a compost that has the potential to suppress S. pogostemonis attack on patchouli plants.